2020
DOI: 10.1007/s10802-020-00623-w
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Pathways of Internalizing Problems from Early Childhood to Adolescence and Associated Adolescent Outcomes

Abstract: Despite trends indicating worsening internalizing problems, characterized by anxiety and depression, there is dearth of research examining gender differences in developmental trajectories of internalizing problems from early childhood to adolescence. Drawing on the UK Millennium Cohort Study (n = 17,206, 49% female), this study examines trajectories of parent-reported, clinically-meaningful (reflecting the top 10%) internalizing problems from ages 3 to 14 years and their early predictors and adolescent outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 66 publications
7
47
1
Order By: Relevance
“…Findings align with studies that have observed significant sex differences in mental health symptoms during the COVID-19 pandemic ( 4 , 72 ). These findings may reflect the interaction of documented increases in internalizing symptoms in girls ( 73 , 74 ) co-occurring with additional pandemic stress. While not a primary focus of the current investigation, future research is warranted to examine the sex effects related to mental health during COVID-19.…”
Section: Discussionmentioning
confidence: 88%
“…Findings align with studies that have observed significant sex differences in mental health symptoms during the COVID-19 pandemic ( 4 , 72 ). These findings may reflect the interaction of documented increases in internalizing symptoms in girls ( 73 , 74 ) co-occurring with additional pandemic stress. While not a primary focus of the current investigation, future research is warranted to examine the sex effects related to mental health during COVID-19.…”
Section: Discussionmentioning
confidence: 88%
“…Both continuity and change over time were observed within trajectory groups, along with common and specific risk factors predicting group membership. Given the extensively documented maladaptive outcomes associated with internalising, externalising, and peer problems when examined individually (e.g., Bevilacqua et al, 2018;Rivenbark et al, 2018;Fairchild et al, 2019;Gutman & McMaster, 2020;Galera et al, 2021;Orri et al, 2018), identification of Percentages of prevalence displayed for chi-square analysis; means and (standard deviations) presented in analysis of variance. Group 1 is nonengagers, Group 2 is low increasing internalising/low stable-decreasing externalising and peer problems, Group 3 is normative, Group 4 is moderate increasing internalising/moderate decreasing-stable externalising and peer problems, Group 5 is low increasing internalising/mixed (moderate-decreasing, high-increasing) externalising/stable peer problems, and Group 6 is high chronic-increasing multimorbid.…”
Section: Discussionmentioning
confidence: 99%
“…Longer term follow-up studies found increases in internalizing symptoms over several years after TBI in both sexes; additionally, younger boys showed greater oppositional defiant problems and older girls showed greater ADHD symptoms ( 6 ). Developmentally, internalizing behavior problems tend to increase more in girls than boys during adolescence ( 74 , 75 ), while externalizing problems are elevated in boys relative to girls ( 76 ). However, we did not identify vulnerability of boys to increases in either outcome domain.…”
Section: Discussionmentioning
confidence: 99%